FINANCIAL RATIO ANALYSIS TO ASSESS PERFORMANCE - Septiani, Veria; Liyundira, Fetri Setyo; Wibisono, Yusuf (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2021)
Purpose of this study was to determine and analyze Financial Ratios to Assess the Performance of the Lumajang Regency Transportation Service. The method used in this research is quantitative with the technique of collecting data documentation on the financial statements of the Department of Transportation in the form of operational reports, budget realization reports and balance sheets which will later be calculated the effectiveness ratio and harmony ratio and adjusted to Government Accounting Standards (SAP). The results of this study are that the Lumajang Regency Transportation Service is still not effective in 2017 and 2019 because there is a deficit in that year. Meanwhile, 2018 has been effective because the criteria are above 100%, namely 101, 39%. So it is said to be effective because the income is greater than the PAD budget and has a surplus from non-operational activities. The compatibility ratio increases every year so that the calculation has a matching criteria every year because all spending is optimized on resources.